Evaluación del desempeño cooperativo de ahorro y crédito con enfoque en el buen vivir, zona sur de Manabí y Santa Elena - Álava Moreira, Pilar Carolina (2016)
The objective of evaluating cooperative performance with a focus on good living in cooperatives in the southern area of Manabí and Santa Elena Province was carried out in three methodological phases: selection of variables, application of the evaluation tool and the plan Of improvement. In the first phase, a determined bibliographical search was carried out on the variables and indicators of cooperative performance based on Cooperativism, Popular and Solidarity Economy, Good Living and Corporate Social Responsibility. In the second phase, the evaluation tool was applied to the credit unions, and workers and partners were also surveyed to compare with the information provided by the managers of the cooperatives. In the last phase an improvement plan was elaborated considering the variables that presented negative valuations, which consists of nine actions with their respective tasks, responsible, times, necessary resources, financing, follow-up indicators and those responsible for the same. It was concluded that the evaluation of the performance of credit unions in the southern area of Manabí and Santa Elena allowed the identification of shortcomings based on the fulfillment of indicators, which can be enhanced based on the proposed improvement plan presented And thus strengthen themselves as institutions.